2020
DOI: 10.1111/bcp.14192
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in EPHA contributes to sensitivity to paclitaxel‐induced peripheral neuropathy

Abstract: Aims: Chemotherapy-induced peripheral neuropathy (PN) is a treatment limiting toxicity of paclitaxel. We evaluated if EPHA genetic variation (EPHA4, EPHA5, EPHA6, and EPHA8) is associated with PN sensitivity by accounting for variability in systemic paclitaxel exposure (time above threshold). Methods:Germline DNA from 60 patients with breast cancer was sequenced. PN was measured using the 8-item sensory subscale (CIPN8) of the patient-reported CIPN20. Associations for 3 genetic models were tested by incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Fifteen of them were nested designs coming from randomized controlled trials (5 case controls 7 , 23 , 24 , 25 , 26 and 10 cohorts 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ), 17 were cohort studies, 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 and 10 were case‐control studies. 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 The studies were conducted in the United States (15 studies 24 , 26 , 27 , 31 , 34 , 35 , 36 , 42 , 48 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen of them were nested designs coming from randomized controlled trials (5 case controls 7 , 23 , 24 , 25 , 26 and 10 cohorts 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ), 17 were cohort studies, 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 and 10 were case‐control studies. 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 The studies were conducted in the United States (15 studies 24 , 26 , 27 , 31 , 34 , 35 , 36 , 42 , 48 , ...…”
Section: Resultsmentioning
confidence: 99%
“…EPHA5 encodes the receptor tyrosine kinase ephrin receptor A5 which guides axonal growth during development 73 . Association of EPHA5 genetic variants with increased risk of paclitaxel‐induced peripheral neuropathy has been replicated in other studies and may be related to the inability to repair injured axons following paclitaxel treatment 69,74 . Although the GWAS that replicated the EPHA5 findings was limited by sample size and included patients treated with both paclitaxel and carboplatin (Table 3), other EPHA genes were also independently associated to CIPN and indicate that ephrin‐A signalling may be a critical function in the response to neuronal injury.…”
Section: Genetic Association Studies Provide Clues To the Molecular Mechanisms Underlying Mta‐induced Peripheral Neuropathymentioning
confidence: 93%
“…Then genes involved in hereditary neuropathy that had previously been reported to increase risk of paclitaxel‐induced neuropathy were investigated, including variants in EPHA5 . Introducing those variants into the neuropathy‐prediction model demonstrated that these genotypes affect a patient’s neuropathy sensitivity after accounting for variability in cumulative paclitaxel exposure 19 . Importantly, a post hoc analysis confirmed that this association for EPHA5 would not have been detected without including measured paclitaxel PKs in the multivariable model.…”
Section: Approaches To Identifying Pgx‐pd Associationsmentioning
confidence: 89%
“…Introducing those variants into the neuropathy-prediction model demonstrated that these genotypes affect a patient's neuropathy sensitivity after accounting for variability in cumulative paclitaxel exposure. 19 Importantly, a post hoc analysis confirmed that this association for EPHA5 would not have been detected without including measured paclitaxel PKs in the multivariable model. In the case of OPRM1, this approach would be attempted by first modeling the morphine-analgesia association and adding OPRM1 genotype as a covariate in the model to see if it explains residual variability in the resulting analgesic effect.…”
Section: Introduce Pgx-pds Into Pk-outcomes Modelmentioning
confidence: 93%